2019
DOI: 10.1002/ejoc.201900417
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Catalyzed Cross‐Dehydrogenative Coupling/Annulation Reaction: A Practical and Efficient Approach to Hydroxyisoindolo[1,2‐b]quinazolinone

Abstract: The palladium‐catalyzed cross‐dehydrogenative coupling (CDC) followed by an intramolecular cyclization between arylquinazolinones and aldehydes has been described. This viable transformation provides a variety of novel substituted hydroxyisoindolo[1,2‐b]quinazolinone compounds in moderate to good yields. Additionally, the reaction is performed with toluene in place of benzaldehyde by using an excess amount of tert‐butyl hydroperoxide (TBHP) as the oxidant in good yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The ubiquitous nature and importance in pharmaceutical research have led to several reported synthetic methodologies for 2,3-fused quinazoline-4(3 H )-ones and their derivatives ( Scheme 1 a) [ 25 , 26 , 27 , 28 ]: (1) N -Cyanamide alkenes react with aldehydes or diketones via intramolecular cyclization difunctionalization [ 18 ], [ 29 , 30 , 31 ]; (2) intramolecular radical cyclization of N3-Alkenyl-tethered quinazolinone [ 32 , 33 , 34 , 35 ]; (3) oxidative cyclization of isatins or isatoic anhydrides with cyclic amines by ring opening strategy [ 36 , 37 ]; (4) cyclic amines undergo a dehydrogenation process including intermolecular and intramolecular cyclization [ 38 , 39 , 40 , 41 ]; (5) 2-Arylquinazolinones undertake a cyclization reaction via transition metal catalysis [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ubiquitous nature and importance in pharmaceutical research have led to several reported synthetic methodologies for 2,3-fused quinazoline-4(3 H )-ones and their derivatives ( Scheme 1 a) [ 25 , 26 , 27 , 28 ]: (1) N -Cyanamide alkenes react with aldehydes or diketones via intramolecular cyclization difunctionalization [ 18 ], [ 29 , 30 , 31 ]; (2) intramolecular radical cyclization of N3-Alkenyl-tethered quinazolinone [ 32 , 33 , 34 , 35 ]; (3) oxidative cyclization of isatins or isatoic anhydrides with cyclic amines by ring opening strategy [ 36 , 37 ]; (4) cyclic amines undergo a dehydrogenation process including intermolecular and intramolecular cyclization [ 38 , 39 , 40 , 41 ]; (5) 2-Arylquinazolinones undertake a cyclization reaction via transition metal catalysis [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, ring-fused quinazolinones play vital roles in the field of medicinal chemistry, and it is meaningful to afford efficient strategies for the synthesis of polycyclic quinazolinone derivatives. Typically, it was reviewed to synthesize 2,3-fused quinazolinones in a number of ways, including difunctionalization of alkenes, ring opening of easily available small rings, dehydrogenative cross-coupling reactions, transition-metal-catalyzed cyclizations, 4 + 2 or 4 + 1 cycloadditions, and other cascade reactions . In these methods, difunctionalization of olefins is usually initiated by free radicals through photoinduction or oxidation, followed by radical tandem addition and cyclization .…”
Section: Introductionmentioning
confidence: 99%
“…To continue our research interest aiming at N ‐heterocycle directed C–H bond functionalization of arenes, herein, we report the first Pd‐catalyzed C–H activation/sulfonylation and halogenation reactions of phthalazindiones. These approaches afford predominantly mono ‐functionalized products under mild and oxidant‐free reaction conditions using a palladium catalytic system and readily accessible and inexpensive reagents as functional group sources (Scheme h).…”
Section: Introductionmentioning
confidence: 99%